(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Online learning has become the need of a time. It is important to compare the effectiveness ofclassroom and online learning teaching research methods that face to face interaction, onlineinteractions are important components of learning and teaching in blended learning environment. Onlinecourses help to reach more time and place bound students. Persistence in an online environment maybe more challenging in classes than public administration classes. The study focuses on finding theopinion of students and teaching fraternity about effectiveness of online learning and classroom learning.This research is descriptive in nature conducted with the help of primary and secondary data. A surveywas conducted through a questionnaire which was sent to teaching fraternity and students. The dataobtained was analyzed with a percentage tool, weighted mean, Standard Deviation and Coefficient ofVariation. Findings can help the academician to understand the issues and challenges faced by studentsand teaching fraternity.